2015
DOI: 10.14260/jemds/2015/725
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Study of Gestational Diabetes Mellitus

Abstract: BACKGROUND: Gestational diabetes mellitus (GDM) is defined as glucose intolerance of variable degree with onset or first recognition during pregnancy. It accounts for 90% of the cases of diabetes mellitus in pregnancy. Family history of diabetes and high body mass index are risk factors for developing gestational diabetes mellitus. In high risk populations, the recurrence risk with future pregnancies is also high. AIM AND OBJECTIVE: 1) to study the proportion of GDM among pregnant women between 24 to 28 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…8 In Khurana M et al study 5.3% of study population had GDM tested by OGTT. 9 American diabetic association (ADA) noticed that 7% of all pregnancies are complicated by GDM. In our study population also GDM prevalance is found to be 7.4%.…”
Section: Discussionmentioning
confidence: 99%
“…8 In Khurana M et al study 5.3% of study population had GDM tested by OGTT. 9 American diabetic association (ADA) noticed that 7% of all pregnancies are complicated by GDM. In our study population also GDM prevalance is found to be 7.4%.…”
Section: Discussionmentioning
confidence: 99%